Lactobacillus cell‐free supernatant as a novel bioagent and biosurfactant against Pseudomonas aeruginosa in the prevention and treatment of orthopedic implant infection. Issue 10 (26th February 2021) - Jeyanathan, Augustina; Ramalhete, Rita; Blunn, Gordon; Gibbs, Hannah; Pumilia, Cyrus Anthony; Meckmongkol, Teerin; Lovejoy, John; Coathup, Melanie J.
Abstract: The hypothesis was that probiotic Lactobacillus species (spp.) or their cell‐free supernatant (CFS) are effective in inhibiting (a) planktonic growth of Pseudomonas aeruginosa (PA), (b) its adhesion to a Ti6Al4V‐alloy surface, and (c) in dispersing biofilm once formed. (a) A planktonic co‐culture containing PA(10 4 colony‐forming unit [CFU]/ml) was combined with either Lactobacillus acidophilus, Lactobacillus plantarum (LP), or Lactobacillus fermentum (LF) at a suspension of 10 4 (1:1) or 10 8 CFU/ml (1:2). Lactobacillus and PA CFUs were then quantified. (b) Ti‐6Al‐4V discs were inoculated with PA followed by supplementation with CFS and adherent PA quantified. (c) Biofilm covered discs were supplemented with Lactobacillus CFS and remaining PA activity quantified. Results showed that whole‐cell cultures were ineffective in preventing PA growth; however, the addition of CFS resulted in a 99.99 ± 0.003% reduction in adherent PA in all Lactobacillus groups ( p < .05 in all groups) with no viable PA growth measured in the LF and LP groups. Following PA biofilm formation, CFS resulted in a significant reduction in PA activity in all Lactobacillus groups ( p ≤ .05 in all groups) with a 29.75 ± 15.98% increase measured in control samples. Supplementation with CFS demonstrated antiadhesive, antibiofilm, and toxic properties to PA.